Epidemiology of malaria and anemia in high and low malaria-endemic North-Eastern districts of India - Shankar, Hari; Singh, Mrigendra Pal; Hussain, Syed Shah Areeb; Phookan, Sobhan; Singh, Kuldeep; Mishra, Neelima (Frontiers in Public Health, 2022)
Anaemia and malaria are the two major public health problems that lead to substantial morbidity and mortality. Malaria infection causes destruction ofdestroys erythrocytes, resulting in low haemoglobin (Hb) levels known as anaemia. Here we report the determinants of anaemia in high and low malaria-endemic areas that would help in understandingunderstand which parasite densities, age, and gender- associated low Hb levels. Therefore, a cross-sectional mass survey (n=8233) was conducted to screen anaemia and malaria in high and low malaria-endemic districts (HMED and LMED) of North-East India. Axillary body temperature was measured using digital thermometer. The prevalence of anaemia was found to be 55.3% (4547/8233), of which 45.1% had mild (2049/4547), 52.1% moderate (2367/4547) and 2.9% had severe anaemia (131/4547). Among anaemic, 70.8% (3219/4547) resided in LMED and rest in HMED. Median age of anaemic population was 12 years (IQR: 7-30). Overall, malaria positivity was 8.9% (734/8233), of which HMED shared 79.6% (584/734) and LMED 20.4% (150/734) malaria burden. The village-wise malaria frequency was concordant to asymptomatic malaria (10-20%), which showed that apparently all of malaria cases were asymptomatic in HMED. LMED population had significantly lower Hb than HMED (standardized beta [β] = -0.067; p<0.0001) and low-density Plasmodium infections had higher Hb levels than high-density infections (β = 0.113; p=0.031). Women of reproductive age had higher odds for malaria (OR: 1.42; 95% CI: 1.00-2.05; p=0.04). Females (β = -0.193; p<0.0001) and febrile individuals (β = -0.029; p=0.008) have shown lower Hb levels, but malaria positivity did not show any effect on Hb. Young children and women of reproductive age are prone to anaemia and malaria. Although there was no relation of malaria with occurrence of anaemia, but we found low-density Plasmodium infections, female gender and LMED were potential determinants of Hb.